Crossing over: Choreographing audiences over borders ‐ Forms and problematics. Issue 2 (1st December 2020) - Munro, Jane
This article considers the potential of participatory artistic practice that debates borders through dance. It also asks why so many dance artists choose this form to debate borders, and what practices are typical of participatory dance investigations of borders. I discuss the range of border debates in works investigating dance and borders, and I begin to consider how privilege is dealt with by the work. I examine how dance works with participation and, alongside, look at the choreographic embodied invitation concerned. Particularly, I examine these questions through the dance work Rope Piece and consider how this dance practice as research generates a collective and participatory process in relation to borders and privilege.